‘Information is power’: A qualitative exploration of co-producing education resources about cardiovascular disease in partnership with women living with lupus - Emily Shantz; Susan J. Elliott; Christine Sperling; May Y. Choi (Women's Health, 2025)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune condition impacting 1 in 2000 people. As 90% of SLE patients are women, and racialized populations experience significantly poorer outcomes, we characterize SLE as gendered, racialized, invisible and episodic. Further compounding these inequities is an elevated risk of cardiovascular disease (CVD) among this population. Crucially, there is a dearth of research evidence as well as public knowledge pertaining to its aetiology and manifestations in women. Indeed, CVD is a primary driver of morbidity and mortality in SLE. Despite calls for improved screening and awareness among this high-risk population, there is a lack of risk prediction tools and patient education resources specific to SLE. Objectives: The objectives of this study were to co-create a lay language patient education resource in partnership with SLE knowledge users, as well as to obtain recommendations on the development of an associated future CVD risk prediction tool designed specifically for this population. Design/Methods: Semi-structured in-depth interviews and a focus group were conducted with women who are SLE patients ( n  = 5) and key informants ( n  = 5), respectively. An integrated knowledge translation approach included a transdisciplinary team of researchers and a patient partner throughout the research process. Results: Participants were knowledgeable about SLE but less informed about the risks of CVD. Few recalled discussing CVD with physician(s), but most were aware of differences in symptoms among men and women. Participants responded positively to the education resource and provided recommendations to improve accessibility, inclusivity and impact for the target audience. Participants agreed that they would use the future SLE-CALCULATOR tool and advised on its design and usability. Conclusions: These results underscore CVD as an urgent women’s health issue and highlight the need for inclusive patient education about the risks of CVD in SLE. The resource discussed herein begins to fill that gap.